2006
DOI: 10.1186/1297-9686-38-4-411
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic study of brown trout from Serbia, based on mitochondrial DNA control region analysis

Abstract: -In order to illuminate the phylogeography of brown trout (Salmo trutta) populations in the Balkan state of Serbia, the 561 bp 5'-end of mtDNA control region of 101 individuals originating from upland tributaries of the Danubian, Aegean and Adriatic drainages were sequenced and compared to corresponding brown trout sequences obtained in previous studies. Among 15 haplotypes found, 14 were considered native, representing the Danubian and Adriatic lineages of the brown trout, while one haplotype (ATcs1), found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 28 publications
2
61
0
Order By: Relevance
“…This haplotype is indigenous for the western Balkan region (Marić et al, 2006). No specimen of the Da23c haplotype indigenous to the broader Iron Gate area was found there, although Marić et al (2006) reported brown trout belonging to the Da23 haplotype group (most likely Da23c) in 1 of 3 sampled individuals from the second fork of this same stream. This might suggest that brown trout of the Da1 haplotype, which were introduced by stocking, overpopulated and supplanted the original trout of the Da23c haplotype.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This haplotype is indigenous for the western Balkan region (Marić et al, 2006). No specimen of the Da23c haplotype indigenous to the broader Iron Gate area was found there, although Marić et al (2006) reported brown trout belonging to the Da23 haplotype group (most likely Da23c) in 1 of 3 sampled individuals from the second fork of this same stream. This might suggest that brown trout of the Da1 haplotype, which were introduced by stocking, overpopulated and supplanted the original trout of the Da23c haplotype.…”
Section: Discussionmentioning
confidence: 94%
“…There is no evidence of their natural occurrence south and southeast of the Alps; regardless, they predominate as native in the headwaters of the upper Danube in Bavaria and in numerous drainages of the Austrian Danube. One possible explanation for the presence of At haplotypes could be uncontrolled stocking with allochthonous, hatchery-reared brown trout of the Atlantic clade, which were introduced in this way into many streams and rivers throughout the Balkans (Marić et al, 2006;Jadan et al, 2010;Simonović et al, 2015) and Europe (Largiadèr and Scholl, 1996;Osinov and Bernatchez, 1996;Hansen et al, 2000;Weiss et al, 2000Weiss et al, , 2001. Two specimens of the same H3 haplotype were recorded in 2010 in the Danube riverbed by Marić et al (2012) near the city of Veliko Gradište at river kilometer 1059.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Bardakci et al (2006) supposed pre-Pleistocene isolation and diversification of the Adriatic, Danubian and Tigris lineages in Turkey. A deep divergence of brown trout within the Black Sea basin has also been indicated (Weiss et al 2001;Duftner et al 2003;Bardakci et al 2006;Marić et al 2006;Turan et al 2009). These findings suggest that beyond the Mediterranean region, the Black Sea basin have had a very important role in the formation of the brown trout diversity.…”
Section: Introductionmentioning
confidence: 83%
“…Impact of stocking with exogenous fish was indicated using microsatellite markers in the Axios River basin (Apostolidis et al 2008b). Marić et al (2006) reported occasional stocking with non-indigenous fish in some rivers of Serbia. Brown trout had also been transported from former Czechoslovakia to Bulgaria during the second half of the 20 th century.…”
Section: Introductionmentioning
confidence: 99%